The Mass Miracle: Public Religion in the Postwar Philippines - de la Cruz, Deirdre (Archīum Ateneo, 2014)
From November 1948 to March 1949, petals of roses fell from the sky on the grounds outside of a Carmelite convent in the town of Lipa, Batangas. The petals and stories about them circulated at local, national, and international levels, giving rise to a variety of interpretations of their significance. Thisarticle examines the rose petals of Lipa as both a phenomenon to be mediated and a medium in its own right, in order to propose the need to rethink the common category of “popular religion.”KEYWORDS: Religion • Catholicism • The Mass Media • Miracles • Transnationalism